If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = -3 + 7x Reorder the terms: 9 + 5x = -3 + 7x Solving 9 + 5x = -3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + 5x + -7x = -3 + 7x + -7x Combine like terms: 5x + -7x = -2x 9 + -2x = -3 + 7x + -7x Combine like terms: 7x + -7x = 0 9 + -2x = -3 + 0 9 + -2x = -3 Add '-9' to each side of the equation. 9 + -9 + -2x = -3 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = -3 + -9 -2x = -3 + -9 Combine like terms: -3 + -9 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| 6.5x-3=11 | | 1-6x=5x+1 | | k-7=-12 | | -2(-2-4n)-4n=-2+5(n+3) | | -7x+5=115+3x | | 1-2x=7x+10 | | -12+x=23 | | 4x^2+2x+16=0 | | 3x+1=-19+x | | 4y*1*9*7y= | | 4g+13500=8500 | | 5x-4(-x+1)=-7 | | 3m-12=36 | | 14u-18v= | | n/9=18 | | 0.6x+11.4=x-5.32 | | 5(9+6x)+7=-12+14x | | -18+9a=8(1+a)-13 | | 10xy-4y= | | 12(v-13)=2v-66 | | 4t^2+24t-27=0 | | 24+y*2=x | | -25=4(5k-7)+3(1+3k) | | 6(2x+1)=12x+3 | | -2(1-10n)=-52+10n | | 48.3/17.3 | | -2(1-10n)=-27+14b | | 0.6x+1.43=x-6.22 | | 6(4b+2)+3b=-27+14b | | (2/3x)-4=5/6 | | 2/3x-4=5/6 | | 5x-25=2x-38 |